Improvements in hand functions and changes in proximal muscle activities in myoelectric prosthetic hand users at home: a case series. Issue 6 (4th December 2022) - Park, Sangsoo; Lee, Jaehyung; Oh, Ye Eun; Lee, Hyun-Joo; Jeon, Inho; Kim, Keehoon; Lee, Song Joo
Abstract : Background: Adaptation in proximal muscles for daily motor tasks after sustained use of a prosthetic hand has not been fully understood. Objectives: This study aimed to investigate changes in hand functions and activities of proximal muscles after multiple weeks of using a myoelectric prosthetic hand at home. Study design: Repeated measures. Methods: Four people with traumatic upper-limb loss used a myoelectric prosthetic hand (bebionic) at home over the 6- to 8-week period. A user survey, Orthotics and Prosthetics User Survey for Upper Extremity Functional Status 2.0, was used to measure upper-limb functions and the degree of using the prosthetic hand each week. Their hand functions, muscle activities, and grip-specific neuromuscular effort were evaluated by the Southampton Hand Assessment Procedure at the preassessment and postassessment sessions (PRE and POST, respectively). Results: All subjects increased Southampton Hand Assessment Procedure scores at PRE compared with POST with subject-specific changes in muscle activations. In a detail, at POST, subject 1 reduced the shoulder muscle activity compared with PRE, while at POST, subject 2 reduced biceps activity compared with PRE. At POST, greater pectoralis activity and reduced trapezius activity were observed in subject 3, and greater activity in those two muscles was found in subject 4 compared with PRE. Conclusion: After multiple weeks of using the myoelectric prosthetic hands, their hand functions during ADL tasks were improved and changes in the muscle activities were found.